ChemInform Abstract: Recent Advances in the Synthesis of New Antimycobacterial Agents Based on the 1H‐1, 2, 3‐Triazoles. Issue 29 (22nd July 2014) - Gonzaga, Daniel Tadeu G.; da Rocha, David R.; da Silva, Fernando de C.; Ferreira, Vitor F.
Abstract Review: 121 refs.